2016
DOI: 10.1155/2016/5802753
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Three Types of Transformer Oil-Based Nanofluids and Comparative Study on the Effect of Nanoparticle Concentrations on Insulating Property of Transformer Oil

Abstract: Nanofluids have the potential to become the alternatives of conventional transformer oil for their exquisite electrical and thermal properties. Three kinds of nanoparticles with distinct conductivities, namely, nonconductive nanoparticle Al2O3, conductive nanoparticle Fe3O4, and semiconductive nanoparticle TiO2, with different concentrations from 5% to 40% w/v were selected and suspended into transformer oil to develop nanofluids. The lightening impulse breakdown strengths of the oil samples with and without n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 22 publications
5
57
0
Order By: Relevance
“…On this basis, the surfaces of the nano-TiO 2 shall be modified with octadecanoic acid [70], and then added into the mineral insulating oil, which can improve the dialectical property of insulating oil and the breakdown voltage in AC state. Wang and Raffia [71] modified mineral insulating oil with 5-40 wt % nano-TiO2, and measured the impulse breakdown voltage of the oil samples before and after modification according to an IEC standard. Under positive pulse conditions, at a certain concentration, the breakdown strength increased to the maximum value firstly, and then, it began to decrease.…”
Section: Effect Of Nanoparticles On the Breakdown Voltage Of Mineral mentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, the surfaces of the nano-TiO 2 shall be modified with octadecanoic acid [70], and then added into the mineral insulating oil, which can improve the dialectical property of insulating oil and the breakdown voltage in AC state. Wang and Raffia [71] modified mineral insulating oil with 5-40 wt % nano-TiO2, and measured the impulse breakdown voltage of the oil samples before and after modification according to an IEC standard. Under positive pulse conditions, at a certain concentration, the breakdown strength increased to the maximum value firstly, and then, it began to decrease.…”
Section: Effect Of Nanoparticles On the Breakdown Voltage Of Mineral mentioning
confidence: 99%
“…Their measurement results showed that the AC breakdown voltage of the nano-SiO2-modified insulating oil was higher than that of the unmodified mineral insulating oil, but the breakdown voltage decreased as the humidity of samples increased. Wang and Raffia [71] modified mineral insulating oil with 5-40 wt % nano-TiO 2 , and measured the impulse breakdown voltage of the oil samples before and after modification according to an IEC standard. Under positive pulse conditions, at a certain concentration, the breakdown strength increased to the maximum value firstly, and then, it began to decrease.…”
Section: Effect Of Nanoparticles On the Breakdown Voltage Of Mineral mentioning
confidence: 99%
“…When the number of nanoparticles is increased, the collision rate between the particles increases due to Brownian motion, but it appears as bridging between two conductors and could lead to breakdown [15]. The question is why an identical phenomenon is also reported for semi-conductive and dielectric-based nanofluids [16]. It was believed that the enhancement of dielectric strength in nanofluids not only depends on the intrinsic properties and interface regions formed between particles, as in solid phases [17][18][19].…”
Section: Introductionmentioning
confidence: 96%
“…are the more popular due to their better stability compared to the pure metals [20,21] and nanotubes [22] as well as low cost and easy manufacturing process, which make them possible for mass production, compromise with their electrical conductivity as well as permittivity. However, breakdown voltage is enhanced up to a certain particle concentration, depending upon the types of nanoparticles and then starts decreasing [23]. It is evident, that magnetite NPs are more capable to captured the free fast electrons; contributes to the streamer development and convert these fast electrons to slow-moving negatively charged particles [24,25].…”
Section: Introductionmentioning
confidence: 99%